Floristic Survey of Vascular Plants in Coastal District Bagerhat of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
This survey provides the basic taxonomic data on the vascular flora of the disasterprone coastal district of Bagerhat. It has explored the occurrence of 964 species of vascular plants under 607 genera and 147 families in this district. About 68.88% of these species are native and 31.12% are exotic to Bangladesh. Pteridophytes are composed of 32 species under 22 genera of 14 families and Gymnosperms of seven species under six genera and five families. Angiosperms are comprised of 693 species of 450 genera and 99 families of Magnoliopsida (dicotyledons) that represent 71.89% of the flora, and 232 species belonging to 129 genera under 29 families of Liliopsida (monocotyledons) that constitute 24.07% of this flora. Fabaceae with 58 species is the largest dicot family, followed by Asteraceae, Euphorbiaceae, Apocynaceae, and Acanthaceae. Poaceae with 68 species is the largest monocot family, followed by Cyperaceae, Orchidaceae, Araceae and Arecaceae. The genus Cyperus is the largest in the study area, which is followed by Fimbristylis, Euphorbia, Ficus, Solanum and Ipomoea. The species Cipadessa baccifera (Roth) Miq. of Meliaceae is rediscovered in Bangladesh. About 63.35% of species of this flora and most of the Magnoliopsida and Liliopsida are herbs, 18.94% shrubs, 15.63% trees, and 1.55% palms. Nearly 70.81% of the species are wild and the rest are planted or cultivated. 17 species are recognized as rare in the study area due to their very restricted occurrence and poor regeneration. Most of the species grow in the fallow lands, roadsides, woodlands, homesteads, marginal lands and scrub jungles. The majority of the species have more than one uses, but most are useful as medicinals (70.39%) and ornamentals (25.57%). Though the study area is under the stress of different threats, its floristic composition is still rich. We strongly recommend adopting adequate effective measures for the conservation and sustainable development of this rich flora of the coastal region.Bangladesh J. Plant Taxon. 29(1): 43-78, 2022 (June)